On the search for coherent radiation from radio pulsars - Smits, J.; Stappers, B.; Macquart, Jean-pierre; Ramachandran, R.; Kuijpers, J. (EDP Sciences, 2003)
We have examined data from pulsars B0950+08 and B0329+54 for evidence of temporally coherent radiation using the modified coherence function (MCF) technique of Jenet et al. (2001). We consider the influence of both instrumental bandpass and interstellar propagation effects. Even after removal of the effects due to the instrumental bandpass, we detect a signature in the MCF of our PSR B0329+54 data which is consistent with the definition of a coherent signal. However, we model the effects due to interstellar scintillation for this pulsar and show that it reproduces the observed signature. In particular, the temporal coherence time is close to the reciprocal of the decorrelation bandwidth due to diffractive scintillation. Furthermore, comparison of the coherence times of three pulsars reported by Jenet et al. (2001) with their expected diffractive decorrelation bandwidths suggests that the detection of coherence in these pulsars is also likely a result of interstellar scintillation, and is not intrinsic to the pulsars.